PENGARUH INTERNALISASI SEMBILAN NILAI ANTI KORUPSI TERHADAP INTENSI PERILAKU KECURANGAN AKADEMIK PADA MAHASISWA BARU UNIVERSITAS ISLAM SUMATERA UTARA: INTENSI PERILAKU KECURANGAN AKADEMIK PADA MAHASISWA BARU UNIVERSITAS ISLAM SUMATERA UTARA - Amelia Trinanda; Annisa Shifa Azzahra; Elsa Putri Anatsya Pasaribu; Indah Wardani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to analyze the influence of internalizing nine anti-corruption values on academic dishonesty intentions among first-year students at Universitas Islam Sumatera Utara (UISU). These values include honesty, responsibility, care, hard work, independence, discipline, simplicity, courage, and fairness. Theresearch uses a descriptive qualitative approach,collecting data through in-depth interviews,observations,and documentation involving new students and academic advisors.The results indicate that the internalization of anti-corruption values plays a crucial role in shaping students’ moral awareness and academic responsibility. Honesty and responsibility emerge as the dominant factors that reduce the intention to cheat or commit plagiarism. Moreover, moral courage and a supportive academic environment strengthen students’ commitment to integrity. In conclusion, the stronger the internalization of anti-corruption values, the lower the students’ intention to engage in academic dishonesty.